Implementation Policy of the Information Security Management System (ISMS) in Bitung Digital City - Theno, Ignatius Rudy; Sendouw, Recky H E; Tumbel, Goinpeace H. (International Journal of Information Technology and Education, 2025)
This study aims to analyze the implementation of the Information Security Management System (ISMS) policy in Bitung City as part of its digital transformation initiative. The policy is crucial to ensure the security, integrity, and availability of public information amid increasing cybersecurity threats in the digital era. This research employs a descriptive qualitative approach using in-depth interviews, document analysis, and observations as data collection techniques. The findings reveal several obstacles in implementing the ISMS policy, including limited human resources, a lack of awareness about information security among civil servants, and the absence of a dedicated information security management team. Budget constraints and inadequate cross-sectoral coordination further hinder effective implementation. Although Bitung City has established regulatory frameworks such as mayoral regulations and regional laws related to e-government systems (SPBE), the enforcement remains suboptimal. The study recommends strengthening human resource capacities, enhancing stakeholder collaboration, and adopting standardized security protocols based on SNI ISO/IEC 27001 to ensure effective ISMS implementation, ultimately supporting Bitung’s vision as a secure and reliable digital city.